Herpes simplex encephalitis (A review) - Satiti Retno Pudjiati, Herning Setijowati (Universitas Gadjah Mada, 2008)
Herpes simplex encephalitis (HSEI is an inflammation of the brain caused by herpes simpleks virus (HSVI. HSE includes serious types. HSE can influence all age group, but most common in those under 20 and over 40 years old. Clinical diagnosis based on clinical presentation, laboratory examination of cerebrospinal fluid (CSFI, even by computerized tomography scan (CT-scan)/magnetic resonance imaging (MRII, electro encephalogram (EEGI is difficult that resulted in nonspecific diagnosis. Polymerase chain reaction (PCRI, and brain biopsy are the best diagnostic test. The main treatment of HSE is non spesific i.e. acyclovir. An early management may decrease the risk of mortality from 80% - 25%. While without treatment the mortality.can reach 70-80% and the prognosis might unfavourable.Key words: encephalitis - HSE - CSF - CT-scan - MRI - EEG